1997
DOI: 10.1111/j.1460-2695.1997.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drawing Strain and Bluing on the Fatigue Strength of Eutectoid Steel Wires

Abstract: The effects of bluing, associated with drawing strain, on the fatigue strength of eutectoid steel wires have been investigated. The fatigue limit increases by bluing and the increase is more significant with higher drawing strain. The peak in the fatigue limit with regard to the drawing strain in the wires, at a strain of 2.5, disappears after bluing. On the other hand, in the ferritic steel wires investigated for comparison, the fatigue limit gradually increases with the drawing strain up to 7.7. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Recent work by Katagiri et al [54,55] with cold-drawn eutectoid steel wires of 0.3 mm diameter showed similar results, i.e., the residual stress is one of the controlling factors of the fatigue limit (as measured by S-N curves). The residual stress in the as-drawn wires was extremely high (around 1,000 MPa) and the fatigue limit around 780 MPa.…”
Section: Fatigue Testsupporting
confidence: 54%
See 1 more Smart Citation
“…Recent work by Katagiri et al [54,55] with cold-drawn eutectoid steel wires of 0.3 mm diameter showed similar results, i.e., the residual stress is one of the controlling factors of the fatigue limit (as measured by S-N curves). The residual stress in the as-drawn wires was extremely high (around 1,000 MPa) and the fatigue limit around 780 MPa.…”
Section: Fatigue Testsupporting
confidence: 54%
“…As the development of a dominant crack from the wire surface under high-cycle fatigue occupies the major part of the fatigue lifetime, an accurate calculation of the fatigue life requires an accurate knowledge of the surface stresses, which are dependent on the external loads and on residual stresses [51], An experimental and numerical investigation of the influence of residual stresses in cold-drawn eutectoid steels on the fatigue limit and on the fatigue life was undertaken some years ago [6,[52][53][54][55]. Llorca and Sanchez-Galvez [52,53] performed fatigue tests at a constant stress range and at different nominal stress ratios (R=cr min / cr max ) on wires with different residual stresses.…”
Section: Fatigue Testmentioning
confidence: 99%
“…The magnitudes of the effects and the mechanisms, however, are not clear enough because they are related to each other. In earlier studies, 4 , 10 the present authors have shown that there exists a drawing strain, ~2.5, where the fatigue limit peaks while the yield stress and ultimate tensile strength still increase monotonically with drawing strain. This was not the case in ferritic steel wires and the peak fatigue limit characteristics with regard to the drawing strain appeared to be peculiar to eutectoid steel wires.…”
Section: Introductionsupporting
confidence: 53%
“…Efforts have been made to improve the fatigue strength of eutectoid steel wires. Drawing strain has been proved to be a controlling parameter, which changes the dislocation structures, 4 the interlamellar spacing 5–8 and the residual stress 9–11 . The microstructure prior to drawing and surface flaws, 9 , 11 as well as damage in the cementite lamellae induced by drawing to a high strain, 10–13 can also influence the fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of the mechanical properties have been conducted to quantify the effects of p [4,5] cementite thickness [6], residual stress [7][8][9] and drawing condition [7]. However, the alloy compositions and fabrication conditions differed in these studies, so the critical factors governing the mechanical properties of heavily cold-drawn steel wires cannot be identified from their results.…”
Section: Introductionmentioning
confidence: 99%